Menangani Disleksia di Era Digital: Peran Teknologi Pendidikan dalam Mendukung Pembelajaran Inklusif di SDN Tegal Besar 03 Jember - Hidayah, Rafika; Hestiningtyas, Peni Lestari; Indah Sari, Noor Halifah; Priawasana, Endra (YASIN, 2025)
This study is driven by the need for effective pedagogical approaches for students with specific learning difficulties, particularly dyslexia, amid the limitations of traditional methods in the digital era. The objective of the research is to determine the effectiveness of educational technology in improving the reading and writing skills of dyslexic students at SDN Tegal Besar 03 Jember. A qualitative case study method was employed, with data collected through observation, interviews, and documentation. The study explores the implementation of technology in an inclusive learning environment, utilizing tools such as Amazon Polly Text-To-Speech, multisensory methods with letter blocks, flashcard media, the Secil application, and the ABC e-book. The findings reveal that the combination of digital tools and multisensory strategies significantly supports the development of reading and writing skills in dyslexic students, particularly in word recognition, comprehension, and basic literacy. Identified challenges include limited access to technological devices, teachers’ readiness in using technology, and varied student responses to the applied methods. The study concludes that the use of educational technology is highly effective in supporting inclusive education for students with dyslexia. Its implications suggest that technology holds substantial potential in fostering a more equitable and accessible education system. The study recommends further research to ensure the sustainability of outcomes and to reinforce the strategic role of technology in future inclusive education.